Low temperature heat capacity and thermodynamic functions of anion bearing sodalites Na8Al6Si6O24X2 (X = SO4, ReO4, Cl, I). (November 2017) - Schliesser, Jacob; Lilova, Kristina; Pierce, Eric M.; Wu, Lili; Missimer, David M.; Woodfield, Brian F.; Navrotsky, Alexandra
Highlights: Heat capacities of sulfate, perrhenate, chloride, and iodide sodalites were measured from 2 K to 300 K. Heat capacities were fitted to equations in three temperature ranges. Standard entropies and Gibbs energies were calculated. All four sodalites undergo a phase transition below room temperature for which thermodynamic parameters were determined. This work is relevant to nuclear waste disposal. Abstract: Heat capacities of sulfate, perrhenate, chloride, and iodide sodalites with the ideal formula Na8 Al6 Si6 O24 X2 (X = SO4, ReO4, Cl, I) were measured from 2 K to 300 K using a Quantum Design Physical Property Measurement System (PPMS). From the heat capacity data, the standard thermodynamic functions were determined. All four sodalites undergo a phase transition below room temperature for which thermodynamic parameters were determined. Additionally, the heat capacity of one of the constituent compounds (NaReO4 ) was measured.